ANALISA SISTEM INFORMASI AKUNTANSI PEMBAYARAN KLAIM JAMINAN HARI TUA (JHT) BPJS KETENAGAKERJAAN BOGOR KOTA - Naura Tursina (2022)
Advances and technological developments in companies, both small and large companies, are increasingly rapidly, due to technological advances, especially in Accounting Information Systems. An Accounting Information System (AIS) is a system that collects accounting data so that a company's accounting department can make the best judgment. BPJS Ketenagakerjaan is one of the business entities that needs to review the accounting system for cash disbursements, as well as claim payments to avoid problems with payment difficulties, calculations, and recording of expenses. The purpose of writing this Final Project is to better understand and explain the application of the Accounting Information System in the payment of Old Age Security Claims at BPJS Ketenagakerjaan Bogor, as well as to find out what documents are needed for the Claim Payment procedure. While the benefits of writing this Final Project Report are that it can add and broaden the author's insight and knowledge regarding the Accounting System for Payment of Old Age Security Claims. Payment of Old Age Security Claims at BPJS Employment Bogor City Branch already has a systematic flow that can be easily accessed by participants when they want to make old age insurance claims, such as checking the completeness of documents, filling out claim forms, verifying personal data, and several other steps. so that participants can easily understand the stages when applying for Old Age Security